2014
DOI: 10.1155/2014/231857
|View full text |Cite
|
Sign up to set email alerts
|

The Morbidity of Reoperative Surgery for Recurrent Benign Nodular Goitre: Impact of Previous Unilateral Thyroid Lobectomy versus Subtotal Thyroidectomy

Abstract: Background. Subtotal thyroidectomy (STT) was previously considered the gold standard in the surgical management of multinodular goitre despite its propensity for recurrence. Our aim was to assess whether prior STT or unilateral lobectomy was associated with increased reoperative morbidity. Methods. A retrospective analysis was conducted extracting data from our endocrine surgical database for the period from January 1991 to June 2006. Two patient groups were defined: Group 1 consisted of patients with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Permanent RLN palsy and hypoparathyroidism were significantly higher in the second group (0.77%vs. 3.4% and 1.5% vs. 5.1%) [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Permanent RLN palsy and hypoparathyroidism were significantly higher in the second group (0.77%vs. 3.4% and 1.5% vs. 5.1%) [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Rudolph et al (18) observed that as compared to patients who had undergone unilateral lobectomy for multinodular goiter, patients who had previously undergone subtotal thyroidectomy had a significantly higher permanent RLN injury rate (3.44% vs. 0.77%). Our results are consistent with those of Kurmann et al, whose retrospective study showed no statistical difference in permanent RLN nerve injury between patients undergoing ipsilateral and those undergoing contralateral redo-surgery (3.8% vs. 0%) (6).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, total thyroidectomy was recommended as the procedure of choice for benign multinodular goiter (2). In the retrospective study of Rudolph and colleagues, total thyroidectomy was demonstrated to be safe and efficacious, especially with the aid of technological advancements like vessel sealing systems and intraoperative nerve monitoring (9). Alongside this, concerns raise due to the thermal spread of the recent vessel sealing systems, which may harm the parathyroid tissue, as well as the recurrent laryngeal nerve.…”
Section: What Is the Evidence In Favor Of Total Thyroidectomy?mentioning
confidence: 99%
“…Rudolph et al demonstrated a significantly increased risk of permanent recurrent laryngeal nerve injury and hypoparathyroidism following previous subtotal thyroidectomy when compared to previous unilateral thyroidectomy (9). Recurrence may arise from the remnant posterolateral tissue that extends into the retrotracheal and retroesophageal areas.…”
Section: Is Subtotal Thyroidectomy An Option?mentioning
confidence: 99%
See 1 more Smart Citation